SUSTAINABLE COMPANY PROFILE DEVELOPMENT FOR MSMEs IN JAKARTA - sarjono, haryadi; Ariska, Popi (SEEIJ (Social Economics and Ecology International Journal), 2023)
The purpose of this research is to assist SMEs in creating a sustainable company profile as an information medium that is needed today and is expected to be used as a solution, means of information, and promotion needed by companies, considering that a company profile is an asset that can be used to enhance an image or image. from the company to establish cooperation with relations, institutions and other relevant agencies. As a result of the pandemic, many MSMEs have sprung up around us and when a marketing opportunity for these MSME products came and were asked to immediately send their company profiles, many could not send them, because they did not have a company profile. It's really unfortunate considering that several opportunities have to be let go, because this is a very good opportunity to increase the credibility of these MSMEs. The research method used is a mixture of quantitative and qualitative with descriptive analysis techniques. This research was conducted from July to November 2022, for 5 months. The research population is only 1 MSME located around the West Jakarta area. Data collection tools and techniques are study guideline questionnaires, interviews, and focus group discussions (FGD). The results of the research have made a company profile where the contents and information in it have been mutually agreed upon using Canva tools, so that it can be changed later if there is new information that needs to be filled in. ,, ,